Effect of hyperbaric oxygenation on mitochondrial function of neuronal cells in the cortex of neonatal rats after hypoxic-ischemic brain damage - Yang,L. (2016)
The timing and mechanisms of protection by hyperbaric oxygenation (HBO) in hypoxic-ischemic brain damage (HIBD) have only been partially elucidated. We monitored the effect of HBO on the mitochondrial function of neuronal cells in the cerebral cortex of neonatal rats after HIBD. Neonatal Sprague-Dawley rats (total of 360 of both genders) were randomly divided into normal control, HIBD, and HIBD+HBO groups. The HBO treatment began immediately after hypoxia-ischemia (HI) and continued once a day for 7 consecutive days. Animals were euthanized 0, 2, 4, 6, and 12 h post-HI to monitor the changes in mitochondrial membrane potential (ΔΨm) occurring soon after a single dose of HBO treatment, as well as 2, 3, 4, 5, 6, and 7 days post-HI to study ΔΨm changes after a series of HBO treatments. Fluctuations in ΔΨm were observed in the ipsilateral cortex in both HIBD and HIBD+HBO groups. Within 2 to 12 h after HI insult, the ΔΨm of the HIBD and HIBD+HBO groups recovered to some extent. A secondary drop in ΔΨm was observed in both groups during the 1-4 days post-HI period, but was more severe in the HIBD+HBO group. There was a secondary recovery of ΔΨm observed in the HIBD+HBO group, but not in the HIBD group, during the 5-7 days period after HI insult. HBO therapy may not lead to improvement of neural cell mitochondrial function in the cerebral cortex in the early stage post-HI, but may improve it in the sub-acute stage post-HI.